The Black list of legal entities: The importance of administrative authorities in creating a favorable business environment in the Serbian market - Kljajić, Maja; Kostić, Marija; Mizdraković, Vule (NBP. Nauka, bezbednosti, policija, 2022)
With the view to creating a favorable business environment and legal security in the market of the Republic of Serbia, a single and centralized database of business entities has been created, in which data on temporary restriction measures are entered. These measures are based on acts of courts, the central bank, the Tax Administration and other competent authorities. The research was conducted on a sample of 1,595 observation units (measures imposed on active business entities) found in the database of active measures of temporary restrictions and published on the website of the Business Registers Agency. The research spanned over almost five years (from 2017 until the first half of 2021). The results of the research show that a total of 1,422 measures of temporary restrictions were imposed by various decision-makers. From the aspect of administrative bodies and courts, a total of 384 measures were imposed in the observed period. The Tax Administration imposed the largest number of temporary restriction measures, with a share of almost 34% of the observed sample. Out of eight potential measures, the results of the research show that two measures of temporary restrictions are imposed in practice, of which the measure preventing the disposal of funds is present in 92.26% of cases.
Keywords: central register, Serbian Business Registers Agency, measures of temporary restrictions, COVID-19